Brainstem leukoaraiosis independently predicts poor outcome after ischemic stroke. (10th May 2018) - Giralt‐Steinhauer, E.; Medrano, S.; Soriano‐Tárraga, C.; Mola‐Caminal, M.; Rasal, R.; Cuadrado‐Godia, E.; Rodríguez‐Campello, A.; Ois, A.; Capellades, J.; Jimenez‐Conde, J.; Roquer, J.
Abstract : Background and purpose: Increased supratentorial white matter hyperintensities volume (S‐WMHV) has been reported to be a predictor of worse outcome in patients with acute ischemic stroke (AIS). However, few studies have focused on less common locations, such as brainstem white matter hyperintensities (B‐WMH), and their relationship to S‐WMHV. This study aimed to examine whether B‐WMH affect clinical outcome after AIS or transient ischemic attack (TIA). Methods: Based on magnetic resonance imaging evidence, B‐WMH were evaluated in 313 prospectively identified patients with AIS/TIA and registered as absent or present. Standardized S‐WMHV was quantified using a validated volumetric image analysis and natural log‐transformed (Log_S‐WMHV). Poor outcome was defined as a modified Rankin Scale score of 3–6 at 3 months after the index event. Results: Brainstem white matter hyperintensities were detected in 57 (18.2%) patients. In unadjusted analyses for outcome, the presence of B‐WMH was associated with worse outcome, compared with patients without B‐WMH ( P = 0.034). In multivariate analysis controlling for age, atrial fibrillation, stroke severity, reperfusion therapies and Log_S‐WMHV, only B‐WMH [odds ratio (OR), 2.46; P = 0.021] and stroke severity (OR, 1.23; P < 0.001) remained independently associated with unfavourable 90‐day modified Rankin Scale score. Patients with B‐WMH were older (OR, 1.06; P < 0.001) and tended to have more hyperlipidaemia (OR, 2.21; P = 0.023) and peripheral arterial disease (OR, 2.57; P = 0.031). Conclusions: Brainstem white matter hyperintensities are an independent predictor of poor outcome after AIS/TIA and this relationship persists after adjustment for important prognostic factors. Our results also show that leukoaraiosis in this location identifies patients with a specific risk factor profile, suggesting differences in the underlying pathogenesis.